(untitled) (مجلة إحالات, 2025)
يعد مفهوم بنية الخطاب من بين المواضيع التي اِهتمت بها الدراسات الأكاديمية في العصر الحديث، وقد نال حظا وافرا من الدراسات النقدية المختلفة في ظل النظريات المعاصرة في الأدب والنقد، تلك النظريات التي اكتشفت في فضاءاته النصية المتنوعة من الأصالة والعمق والخصوبة والثراء ما أغراها بالمزيد من التوغل في عوالم الإبداع، وفي ضوء هذه المعطيات الجديدة اِتسعت دائرة الإهتمام ببنية الخطاب لتتجاوز الدراسات الأدبية والنقدية إلى حقول معرفية متعددة كعلم النفس، علم الاجتماع، الأنثروبولوجيا، ليتبوأ الصدارة وسط الزخم الهائل من الإبداعات في العصر الحالي، من هنا سنحاول تقديم مسحة عامة عن معنى البنية والخطاب مع رصد المقاربات المنهجية حسب التصور العربي والغربي والبحث عن إمتداداتهما في العمل الإبداعي الأدبي. Abstract: The structure of speech, this concept is considered one of the subjects that are interesting by academic studies in the modern time, it took the huge part of critical studies falling within contemporary theory of Literature and criticism, these theories discovered in the different texts of speech a lot of originality and richness which make it more creative. In the light of these new concepts, the circle of interest in structure of speech has been extended to reach different fields of knowledge such as psychology, sociology and anthropology, however it occupies the place of leader between the congestion of actual creations. So we will try to give a global view about The concept of structure and speech with methodological approachs Within arabic and western points of view, then we search for theirs extensions in the creative literary work.